2022
DOI: 10.2174/1570159x19666211102154311
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies, Chemistry and Therapeutic Insights of Multi-target Directed Ligands as Antidepressant Agents

Abstract: : Depression is one of the major disorders of the central nervous system worldwide and causes disability and functional impairment. According to the World Health Organization, around 265 million people worldwide are affected by depression. Currently marketed antidepressant drugs take weeks or even months to show anticipated clinical efficacy but remain ineffective in treating suicidal thoughts and cognitive impairment. Due to its multifactorial complexity, single-target drugs did not always produce satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…Currently, many depressed patients become insensitive to medication and even further exhibit refractory depression [ 9 , 10 ]. Because there is no systematic theoretical guidance, the diagnosis and treatment often face a dilemma [ 11 ]; antidepressant treatment options are limited and, in some cases, ineffective [ 12 ]. In our previous studies, we have proposed a hypothesis of mood alterations in depression from the basic emotional aspects [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many depressed patients become insensitive to medication and even further exhibit refractory depression [ 9 , 10 ]. Because there is no systematic theoretical guidance, the diagnosis and treatment often face a dilemma [ 11 ]; antidepressant treatment options are limited and, in some cases, ineffective [ 12 ]. In our previous studies, we have proposed a hypothesis of mood alterations in depression from the basic emotional aspects [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole is reported to exhibit a broad range of applications in pharmaceutical and industrial applications [ 14 ]. For example, this organic framework is sought in many drug pharmacophores, such as angiotensin II inhibitors, anti-inflammatory agents [ 91 ], anticancer agents, and building blocks of naturally occurring products [ 13 , 92 ]. The imidazole ring is a well-observed ligand in metalloenzymes, and its imidazolium salts are also well-exploited to serve as excellent precursors of stable carbene ligands in various metal complexes [ 93 , 94 ].…”
Section: Modern Synthetic Methods For Substituted Imidazole Derivativesmentioning
confidence: 99%
“…Despite a long history of conventional use and safety credence for natural products, they have woefully received less attention than chemically synthesized drugs [ 36 ]. Neurohealth-promoting properties of natural products ranging from improving cognitive function to alleviating NDD’s symptoms including depression, memory loss, and poor cognition are being practiced by traditional medicine practitioners [ 37 - 39 ]. Studies have reported the use of various plant and animal species as pro-cognitive agents and treatment options for several neurological and psychological disorders [ 40 - 42 ].…”
Section: Role Of Natural Products In Nddsmentioning
confidence: 99%
“…In ethidium bromide-induced multiple sclerosis experimental rat models, apigenin prevented neurochemical and neurobehavioural defects by modulating the levels of c-JNK/p38MAPK and myelin basic protein in brain and CSF homogenate. Moreover, the imbalanced levels of apoptotic markers (Bax, Bcl-2, caspase-3) and inflammatory cytokines (TNF-α, IL-1β) were reduced by apigenin treatment [ 39 ]. Also, the oxidative stress amelioration potential of apigenin in SH-SY5Y [ 103 ] and dendritic cells of experimental autoimmune encephalomyelitis (EAE) mice [ 104 ] has been documented.…”
Section: Role Of Natural Products In Nddsmentioning
confidence: 99%